2011
DOI: 10.1523/jneurosci.5018-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

The Locus Ceruleus Responds to Signaling Molecules Obtained from the CSF by Transfer through Tanycytes

Abstract: Neurons can access signaling molecules through two principal pathways: synaptic transmission ("wiring transmission") and nonsynaptic transmission ("volume transmission"). Wiring transmission is usually considered the far more important mode of neuronal signaling. Using embryonic chick locus ceruleus (LoC) as a model, we quantified and compared routes of delivery of the neurotrophin nerve growth factor (NGF), either through a multisynaptic axonal pathway or via the CSF. We now show that the axonal pathway from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…One possibility is that MCH translocates into the neuropil through tanycytes, which are specialized ependymal cells lining the base of the lateral and third cerebral ventricles. For example, radiolabeled nerve growth factor injected into the CSF has been shown to translocate from the CSF through tanycytes and accumulate in the locus coeruleus (Feng et al, 2011). Moreover, the anorectic adipokine, leptin, is trafficked from the median eminence to mediobasal hypothalamic neurons via tanycyte-mediated transport into CSF (Balland et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that MCH translocates into the neuropil through tanycytes, which are specialized ependymal cells lining the base of the lateral and third cerebral ventricles. For example, radiolabeled nerve growth factor injected into the CSF has been shown to translocate from the CSF through tanycytes and accumulate in the locus coeruleus (Feng et al, 2011). Moreover, the anorectic adipokine, leptin, is trafficked from the median eminence to mediobasal hypothalamic neurons via tanycyte-mediated transport into CSF (Balland et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CSF ghrelin appears to have a higher accessibility, as compared to other hormones, and quickly access to different brain areas. Interestingly, it has been shown that noradrenergic neurons of the avian LoC accumulate CSF components, which are initially endocytosed and transcytosed by ependymal cells (Feng et al, 2011). This uptake of molecules from the CSF is highly selective as internalizes nerve growth factor and urotensin-1, but not other neurotrophic factors (Feng et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that noradrenergic neurons of the avian LoC accumulate CSF components, which are initially endocytosed and transcytosed by ependymal cells (Feng et al, 2011). This uptake of molecules from the CSF is highly selective as internalizes nerve growth factor and urotensin-1, but not other neurotrophic factors (Feng et al, 2011). Here we report that fluorescein-IR cells are present in the LoC, which presumably lacks GHSR-1a (Zigman et al, 2006, Perello et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Tanycytes are known to extract different substances from the CSF, including glucose, glutamate, neuropeptides, NGF, and transforming growth factors. After intracellular transport, these substances can be released from tanycyte processes to adjacent neurons, thus contributing to intercellular signaling (Ugrumov and Mitskevich, ; Rodriguez et al, ; Feng et al, ). The fact that not all ependymal cells stained positive for fetuin‐A further supports an active and controlled process, rather than nonspecific transport of fetuin‐A over the CSF brain barrier.…”
Section: Discussionmentioning
confidence: 99%